Nanotubes and nanowires - Rao, C. N. R. 1934-; Govindaraj, A.; Panchakarla, Leela Srinivas (RSC nanoscience & nanotechnology ;, 2022)
Nanotubes (both of carbon and inorganic materials) can be made in a variety of ways, demonstrating a wide range of fascinating properties. Many of these, such as high mechanical strength and interesting electronic properties relate directly to potential applications. Nanowires have been made from a vast array of inorganic materials and provide great scope for further research into their properties and possible applications. Chapters in this book systematically describe the fundamentals and applications of nanotubes and nanowires, providing a comprehensive and up-to-date survey of the research area, including synthesis, characterisation, properties and applications. This new edition of Nanotubes and Nanowires includes an extensive list of references and is ideal both for graduates needing an introduction to the field of nanomaterials as well as for professionals and researchers in academia and industry. Review of Nanotubes and Nanowires 1st Edition: This book does a truly admirable job of summarizing the literature in this rapidly changing field. Journal of the American Chemical Society, 2006, 128, 4163-4164 Review of Nanotubes and Nanowires 2nd Edition: Rao and Govindaraj do a superb job of distilling the huge literature on inorganic nanotubes and nanowires. Chemistry & Industry, 2011, 24, 27